Developing policy research and outreach partnerships: the role and impact of the Network of IFPRI Associates (NIA) - Rhoe, Valerie; Babu, Suresh Chandra (International Food Policy Research Institute, 2002)
This paper summarizes the papers and proceedings of a workshop held at the International Food Policy Research Institute in Washington, D.C., January 23-24, 2002. the four objectives of the workshop were: (1) to increase the knowledge of network associates abut IFPRI Divisions and their work; (2) to share relevant knowledge among network associates; (3) to share information between IFPRI researchers and network associates; and, (4) to discuss ways to increase the network's impact.